Motivasi Belajar Kewirausahaan Dan Faktor Yang Mempengaruhinya Bagi Mahasiswa Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah Dan Keguruan UIN Alauddin Makassar - Jusriana, Andi; Suarga; Ahmad, Fandi (MACCA : Science-Edu Journal, 2024)
The problem formulation of this research is based on the background described above. The research problems can be summarized as follows: How is the interest in learning entrepreneurship among students of the Arabic Language Education Department? How do Arabic Language Education students pay attention to the assignments in the entrepreneurship course given by the lecturers? How is the enthusiasm of Arabic Language Education students during the entrepreneurship learning process? What is the level of academic achievement in the entrepreneurship course for Arabic Language Education students? And what factors influence the motivation to learn entrepreneurship in Arabic Language Education? The purpose of this research is to find out the level of interest in learning entrepreneurship among students of the Arabic Language Education Department at the Faculty of Tarbiyah and Teaching, UIN Alauddin Makassar, to understand their attention to entrepreneurship course assignments, to determine their enthusiasm for learning entrepreneurship, to evaluate the academic performance in the entrepreneurship course, and to identify the factors that influence their motivation to learn entrepreneurship. This research uses a descriptive qualitative method. Data collection was conducted through interviews. The results of the research indicate that the interest of Arabic Language Education students in learning entrepreneurship is relatively very satisfactory because it provides them with opportunities for entrepreneurship without depending on the government or others, thereby fostering a strong sense of independence. The students' level of attention to completing entrepreneurship assignments given by lecturers is high, as they gain new knowledge and experiences and can directly observe real entrepreneurial activities in the field, which also cultivates a spirit of creativity and innovation. The students’ enthusiasm during entrepreneurship learning sessions is excellent, as they realize that entrepreneurship activities offer unique value, especially in fostering the courage to take risks, enabling them to face challenges effectively. The academic achievement in the entrepreneurship course among the students generally shows outstanding result.